Septic shock with multiple organ dysfunction syndrome, disseminated intravascular coagulation and mucormycosis following unsafe abortion: a case of acute infectious purpura fulminans - Mundhra, Rajlaxmi; Gill, Poonam; Singh, Sudhir Kumar; Singla, Deepak; Vishwakarma, Anushka; Chaturvedi, Jaya (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
A woman in her early thirties presented to the emergency department in the 2nd week of her illness. She had a history of self-MTP kit intake at 12 weeks gestation followed by dilatation and curettage by the local practitioner for incomplete abortion. She started having a fever and developed blisters all over her body. On presentation, thorough history and examination confirmed sepsis and septic shock. Management continued with the sepsis campaign recommendation 2021 in the critical care unit. In the sixth week of her stay, she developed methicillin-resistant Staphylococcus aureus (MRSA) and mucormycosis further complicating her management. The patient succumbed to her illness after 6 weeks of aggressive treatment including daily wound debridement, amputation, and colostomy. This case emphasizes the importance of contraception use and the prevention of unwanted pregnancy. Further to reduce maternal morbidity and mortality, safe abortion practices should be opted for.